Overexpression of SlGATA17 Promotes Drought Tolerance in Transgenic Tomato Plants by Enhancing Activation of the Phenylpropanoid Biosynthetic Pathway - Zhao, Tingting; Wu, Tairu; Pei, Tong; Wang, Ziyu; Yang, Huanhuan; Jiang, Jingbin; Zhang, He; Chen, Xiuling; Li, Jingfu; Xu, Xiangyang (Frontiers in Plant Science, 2021)
GATA transcription factors (TFs) are widely distributed in eukaryotes. Some GATA TFs have been shown to be related to photosynthesis, germination, circadian rhythm, and other functions in plants. Our previous study found that some members of this family have obvious responses when tomato plants are subjected to drought stress, in which the SlGATA17 gene is significantly upregulated. To further verify the function of this gene under drought stress, we constructed tomato lines with this gene overexpressed. Phenotypic and physiological indicators indicated that the SlGATA17-overexpressing plants were more drought tolerant than the wild-type plants. Transcriptomic sequencing results showed that the overexpression of the SlGATA17 gene improved the activity of the phenylpropanoid biosynthesis pathway. The PAL enzyme activity assay results confirmed that the initial activity of this pathway was enhanced in transgenic plants, especially in the initial response stage, indicating that the SlGATA17 gene regulates the drought resistance of tomato plants by regulating the activity of the phenylpropanoid biosynthesis pathway.